مفھوم الامانة في التراث الأدبي للامام علي ( علیھ السلام ) - دراسة تحلیلیة (Journal of the College of Education for Women, 2019)
the boot of honesty in the dictionary the term linguistic and religiousheritage, literary and Islamic Sufi thought, and concept in the literature of ImamAli, peace is upon him. And studied the summary first concerns its presence in theliterature and implications and directions, either the second part, has cared for theanalytical study has found research that safe weight was the counterpart of thepersonality of the Imam accompanied the character most prominent in hischaracter, namely, (courage), it has struggled to deliver a impact of humanity in histime and after the word and deed, It was based on the imagination in the formationof images sensual and intellectual, to his persuasion of the evidence and arguments,which was adopted methods of art, including condensation and brevity andnarrative including the metaphor and metonymy and bilateral discrepancy,including the rhythm Pacific report, ie, the wisdom of the rhythm of higher rebukeand violent tastefully artistic high to meet the biography of his life the confluenceof thought and imagination and passion.